A survey of the Sli gene in wild and cultivated potato - Mercedes Ames; Andy Hamernik; William Behling; David S. Douches; Dennis A. Halterman; Paul C. Bethke (Plant Direct, 2024)
Abstract Inbred‐hybrid breeding of diploid potatoes necessitates breeding lines that are self‐compatible. One way of incorporating self‐compatibility into incompatible cultivated potato (Solanum tuberosum) germplasm is to introduce the S‐locus inhibitor gene (Sli), which functions as a dominant inhibitor of gametophytic self‐incompatibility. To learn more about Sli diversity and function in wild species relatives of cultivated potato, we obtained Sli gene sequences that extended from the 5′UTR to the 3′UTR from 133 individuals from 22 wild species relatives of potato and eight diverse cultivated potato clones. DNA sequence alignment and phylogenetic trees based on genomic and protein sequences show that there are two highly conserved groups of Sli sequences. DNA sequences in one group contain the 533 bp insertion upstream of the start codon identified previously in self‐compatible potato. The second group lacks the insertion. Three diploid and four polyploid individuals of wild species collected from geographically disjointed localities contained Sli with the 533 bp insertion. For most of the wild species clones examined, however, Sli did not have the insertion. Phylogenetic analysis indicated that Sli sequences with the insertion, in wild species and in cultivated clones, trace back to a single origin. Some diploid wild potatoes that have Sli with the insertion were self‐incompatible and some wild potatoes that lack the insertion were self‐compatible. Although there is evidence of positive selection for some codon positions in Sli, there is no evidence of diversifying selection at the gene level. In silico analysis of Sli protein structure did not support the hypothesis that amino acid changes from wild‐type (no insertion) to insertion‐type account for changes in protein function. Our study demonstrated that genetic factors besides the Sli gene must be important for conditioning a switch in the mating system from self‐incompatible to self‐compatible in wild potatoes.